PENERAPAN METODE BERCERITA MELALUI MEDIA UNTUK MENGEMBANGKAN BAHASA ANAK - Siti Utari (UNISAN JURNAL, 2024)
This examination expects to decide the use of narrating techniques through kids’ language understanding media. The kind of exploration did is field research which means to tackle issues in day to day existence. Case research centers around a case seriously and exhaustively in regards to the foundation of the flow circumstance. In view of the aftereffects of study hall activity research which has been brought out through a few cycles, beginning from cycle I and cycle II and in light of the relative multitude of conversations and what has been finished, it tends to be reasoned that the utilization of the narrating strategy is through the narrating technique. delineated story media, dolls, creature formed manifestations produced using mica cake, and planel loads up can foster youngsters’ language at Fishes Bangsa Kindergarten. This should be visible from the expansion in understudies’ language improvement who have arrived at the generally excellent improvement evaluation standard (BSB), where in pre-research understudies who created by assumptions were just 6 understudies out of a sum of 20 understudies. Subsequent to directing exploration, in the main cycle the understudies who created by assumptions expanded to 8 understudies or 40%, and in the second cycle the understudies who created by assumptions expanded again to 16 understudies or 80%. Understudies have arrived at the foreordained evaluation norms, in particular 80% of the quantity of youngsters. Subsequently, the activity speculation proposed by the creator was replied during the time spent carrying out the homeroom activity research that the creator did, in particular "the utilization of narrating strategies through media can foster youngsters’ language in Fishes Bangsa Kindergarten